Cognitive and Attitudinal Factors Involved in Mathematical Performance in High School Students - Stelzer, Florencia (2023)
Background: Different authors indicate that attitudes towards mathematics, executive functions, and prior mathematical knowledge represent central variables in mathematics learning; however, there is no evidence about their joint and relative contribution to the prediction of mathematics performance in high school students. Main goal: To analyze the contribution of perceived competence, mathematics enjoyment, executive functions, and prior knowledge in the prediction of mathematics performance in first and second-year high school students. Method: Participants were 178 students who were enrolled in the first two years of high school (Mage = 13.4 years, SD = .32; 45.5% boys). Results: The set of variables explained 49% of the variance in mathematics performance, with perceived competence, mathematics enjoyment, and working memory being significant predictors. No differences were found in the strength of the relationship between working memory and mathematics performance between the school years analyzed. Conclusions: The evaluated attitudinal aspects and working memory represent important variables to predict performance in mathematics performance at the secondary level. Authorship contributionAll authors contributed to all aspects of the work.